(untitled) (Entrepreneurship Journal for Finance and Business, 2022)
The research aims to activate forensic accounting within the Iraqi environment by the auditor by working as a judicial expert specialized in the accounting aspect (forensic accountant) to provide judicial services to the legal authorities represented by judicial support services. The problem of the research is not giving a role to a person who is scientifically and practically qualified to look into the relevant issues as a judicial expert specialized in the accounting aspect (judicial accountant) in the Iraqi courts. The researcher concluded that: activating forensic accounting is a remedy for the weakness in the performance level of judicial experts within the Iraqi environment, and that the auditor works to strengthen judicial services and possesses extensive scientific and practical experience to address the shortcomings of the current experts specialized in the accounting aspect. And one of the most important conclusions reached by the researcher is the presence of reluctance to consider issues related to the relevant jurisdiction, which led to the failure to resolve those issues due to the selection of unsuitable people, which led to a weakness in the judicial experience and thus a reason for weakness in the decisions issued by the legal authorities.